Combining IR and X‐ray microtomography data sets: Application to Itokawa particles and to Paris meteorite. (29th June 2020) - Dionnet, Zelia; Brunetto, Rosario; Aléon‐Toppani, Alice; Rubino, Stefano; Baklouti, Donia; Borondics, Ferenc; Buellet, Anne‐Cécile; Djouadi, Zahia; King, Andrew; Nakamura, Tomoki; Rotundi, Alessandra; Sandt, Christophe; et al.
Abstract: In the near future, a new generation of sample return missions (Hayabusa2, OSIRIS‐REx, MMX, etc.) will collect samples from small solar system bodies. To maximize the scientific outcome of laboratory studies and minimize the loss of precious extraterrestrial samples, an analytical sequence from less destructive to more destructive techniques needs to be established. In this work, we present a combined X‐ray and IR microtomography applied to five Itokawa particles and one fragment of the primitive carbonaceous chondrite Paris. We show that this analytical approach is able to provide a 3‐D physical and chemical characterization of individual extraterrestrial particles, using the measurement of their 3‐D structure and porosity, and the detection of mineral and organic phases, and their spatial co‐localization in 3‐D. We propose these techniques as an efficient first step in a multitechnique analytical sequence on microscopic samples collected by space missions.